2010
DOI: 10.1111/j.1749-6632.2010.05553.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis through cysteine oxidation: implications for fibrotic lung disease

Abstract: Tissue fibrosis is believed to be a manifestation of dysregulated repair following injury, in association with impaired reepithelialization, and aberrant myofibroblast activation and proliferation. Numerous pathways have been linked to the pathogenesis of fibrotic lung disease, including the death receptor Fas, which contributes to apoptosis of lung epithelial cells. A redox imbalance also has been implicated in disease pathogenesis, although mechanistic details whereby oxidative changes intersect with profibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…Lung fibrosis is believed to be a manifestation of dysregulated repair following injury, in association with impaired reepithelialization and aberrant myofibroblast activation and proliferation (23). Numerous pathways have been linked to the pathogenesis of fibrotic lung disease, including Fas (4,49), which contributes to apoptosis of lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lung fibrosis is believed to be a manifestation of dysregulated repair following injury, in association with impaired reepithelialization and aberrant myofibroblast activation and proliferation (23). Numerous pathways have been linked to the pathogenesis of fibrotic lung disease, including Fas (4,49), which contributes to apoptosis of lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…While S -glutathionylation of Prdx6 is protective, the second protein has been identified as a GSTP target amplifies apoptosis. The death receptor Fas is S -glutathionylated on Cys294 (Fas-SSG) prior to the onset of apoptosis [14,17]. Fas is a member of the tumor necrosis receptor superfamily such that the binding of ligand leads to the downstream activation caspase 8- or 10- mediated apoptosis.…”
Section: Redox-mediated Post-translational Modificationsmentioning
confidence: 99%
“…It has been demonstrated that depending on the degree of intracellular oxidative stress, which depends on the redox balance between ROS generation and antioxidant mechanisms, caspases can be activated or inhibited [29]. Oxidation of cysteines in proteins is known to act as a regulatory event that affects protein function [34]. In our study, altering the intracellular concentration of NAC might shed light on the relationship among paclitaxel-induced changes in the susceptibility of caspase cysteines to redox modification, caspase activities, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%